Have fun with these expressions!

Algebra Level 4

Let a 1 , a 2 , a 3 , , a n a_1, a_2, a_3, \cdots, a_n be positive real numbers with n 3 n \geq 3 and a 1 a 2 a 3 a n = 1 a_1a_2a_3 \cdots a_n = 1 . If

a 1 ( 1 + a 2 ) 2 ( 1 + a 3 ) 3 ( 1 + a n ) n = n n a_1(1+a_2)^2(1+a_3)^3\ldots(1+a_n)^n=n^n

find the value of

a 1 n 1 ( 1 a 2 + 1 a 3 + 1 a 4 + + 1 a n ) \frac{a_1}{n-1} \left(\frac{1}{a_2} + \frac{1}{a_3} + \frac 1{a_4} + \cdots + \frac{1}{a_n}\right)

n n n ! n! n ! 2 \frac{n!}{2} n n n^n n 2 \frac{n}{2} n n 4 \frac{n^n}{4}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sándor Daróczi
Aug 29, 2017

Fix an integer k k such that 2 k n 2 \leq k \leq n . We start by applying weighted AM-GM inequality to the positive numbers 1 k 1 \frac{1}{k-1} and a k a_k with weights k 1 k-1 and 1 1 respectively:

1 + a k k = ( k 1 ) 1 k 1 + a k k ( ( 1 k 1 ) k 1 a k 1 ) 1 k = ( a k ( k 1 ) k 1 ) 1 k \frac{1+a_k}{k} = \frac{(k-1)\frac{1}{k-1}+a_k}{k} \geq ((\frac{1}{k-1})^{k-1} \cdot {a_k}^1)^{\frac{1}{k}} = (\frac{a_k}{(k-1)^{k-1}})^{\frac{1}{k}}

Therefore it follows that ( 1 + a k ) k k k ( k 1 ) k 1 a k (1+a_k)^k \geq \frac{k^k}{(k-1)^{k-1}}a_k for every 2 k n 2 \leq k \leq n . Equality holds when a k = 1 k 1 a_k=\frac{1}{k-1} .

Multiplying together these inequalities we obtain:

a 1 ( 1 + a 2 ) 2 ( 1 + a 3 ) 3 ( 1 + a n ) n a 1 a 2 a 3 a n 2 2 1 1 3 3 2 2 n n ( n 1 ) n 1 = a 1 a 2 a 3 a n n n = n n a_1(1+a_2)^2(1+a_3)^3 \ldots (1+a_n)^n \geq a_1a_2a_3 \ldots a_n \cdot \frac{2^2}{1^1} \cdot \frac{3^3}{2^2} \cdot \ldots \cdot \frac{n^n}{(n-1)^{n-1}} = a_1a_2a_3 \ldots a_n \cdot n^n = n^n

Equality occurs only when a k = 1 k 1 a_k=\frac{1}{k-1} for every 2 k n 2 \leq k \leq n .

Since we did not use the value of a 1 a_1 in this reasoning, we may assume that a 1 = ( n 1 ) ! a_1=(n-1)! so that the condition a 1 a 2 a n = 1 a_1a_2 \ldots a_n=1 is met. Thus we have shown that the conditions are fulfilled only by these values of a 1 , , a n a_1, \ldots, a_n , hence the value of our desired expression is easy to determine now:

a 1 n 1 ( 1 a 2 + 1 a 3 + + 1 a n ) = ( n 1 ) ! n 1 ( 1 + 2 + + n 1 ) = ( n 2 ) ! ( n 1 ) n 2 = n ! 2 \frac{a_1}{n-1}(\frac{1}{a_2} + \frac{1}{a_3} + \ldots + \frac{1}{a_n}) = \frac{(n-1)!}{n-1}(1 + 2 + \ldots + n-1) = (n-2)! \cdot \frac{(n-1)n}{2} = \frac{n!}{2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...